Magic Castle Readers : Yes, No, Little Hippo : A Book About Safety - Moncure, Jane Belk; DeSantis, Susan, 1964- (Mankato, MN : The Childs World, 2013)
After experiencing several falls and bumps, Little Hippo discovers how to play safely and have fun without the danger of accidents.
Keywords: Hippopotamus; Juvenile fiction; Accidents -- Prevention; Juvenile fiction; Children's book